Knowledge on STIs, HIV/Aids, Premarital Sexual Behavior among Janjati Adolescents - Yadav, Raj Kumar (Academic Voices: A Multidisciplinary Journal, 2018)
This paper focuses on the knowledge of STIs, HIV/AIDS, and attitude on condom use with premarital sexual behavior among the Janjati adolescents of Pathlaiya, Bara district. The results show that knowledge on STIs and HIV/ AIDS, use of condom and premarital sexual behaviour seemed high in the adolescents. Magar adolescents were found better regarding the knowledge on STIs, HIV/AIDS, attitude towards condom use and premarital sexual behavior in comparison to Tamang and Gurung adolescents. It is recommended that various awareness programme should be conducted to prevent further spread of HIV/AIDS among the Janjati adolescents.